Why did a vehicle stop? A methodology for detection and classification of stops in vehicle trajectories. Issue 10 (2nd October 2020) - Rehrl, Karl; Gröchenig, Simon; Kranzinger, Stefan
ABSTRACT: Trajectory data mining is a lively research field in the domain of spatio-temporal data mining. Trajectory pattern mining comprises a set of specific pattern mining methods, which are applied as consecutive steps on a trajectory with the goal to extract and classify re-occurring spatio-temporal patterns. Despite the common nature and frequent usage of such methods by the GIScience community, a methodological approach is missing so far, especially when it comes to the use of machine learning-based classification methods. The current work closes this gap by proposing and evaluating a machine learning-based 3-steps trajectory data mining methodology using the detection and classification of stop points in vehicle trajectories as example. The work describes in detail the applied methodologies with respect to the three mining steps 'stop detection', 'feature extraction' and 'classification in traffic-relevant and non-traffic-relevant stops' and evaluates six machine learning-based classification algorithms using a real-world dataset of 15, 498 vehicle trajectories with 5, 899 detected stops (thereof 2, 032 manually classified). Due to its exemplary nature, the presented methodology is suited to act as blueprint for similar trajectory data mining problems.